ALMA Survey of Orion Planck Galactic Cold Clumps (ALMASOP): The Warm-envelope Origin of Hot Corinos - Shih-Ying Hsu; Sheng-Yuan Liu; Doug Johnstone; Tie Liu; Leonardo Bronfman; Huei-Ru Vivien Chen; Somnath Dutta; David J. Eden; Neal J. Evans II; Naomi Hirano; Mika Juvela; Yi-Jehng Kuan; et al. (The Astrophysical Journal, 2023)
Hot corinos are of great interest due to their richness in interstellar complex organic molecules (COMs) and the consequent potential prebiotic connection to solar-like planetary systems. Recent surveys have reported an increasing number of detected hot corinos in Class 0/I protostars; however, the relationships between their physical properties and the hot-corino signatures remain elusive. In this study, our objective is to establish a general picture of the detectability of hot corinos by identifying the origins of the hot-corino signatures in the sample of young stellar objects (YSOs) obtained from the Atacama Large Millimeter/submillimeter Array Survey of Orion Planck Galactic Cold Clumps project. We apply spectral energy distribution modeling to our sample and identify the physical parameters of the modeled YSOs directly, linking the detection of hot-corino signatures to the envelope properties of the YSOs. Imaging simulations of the methanol emission further support this scenario. We therefore posit that the observed COM emission originates from the warm inner envelopes of the sample YSOs, based on both the warm region size and the envelope density profile. The former is governed by the source luminosity and is additionally affected by the disk and cavity properties, while the latter is related to the evolutionary stages. This scenario provides a framework for detecting hot-corino signatures toward luminous Class 0 YSOs, with fewer detections being observed toward similarly luminous Class I sources.